Efficacy and Safety of First-Line Palliative Chemotherapy with Fluorouracil Plus Leucovorin, Oxaliplatin, and Docetaxel (FLOT) in HER2-Negative Metastatic Gastric or Gastroesophageal Junction Adenocarcinoma: A Single-Institutional Real-World Experience from Eastern India - Chaudhuri, Tamojit; Bankira, Jaishree; Upadhyay, Amitabh Kumar; Panda, Rahul; Pandey, Vanita; Mitra, Sujata; Mukherjee, Sopia (South Asian Journal of Cancer, 2024)
Background Fluorouracil plus leucovorin, oxaliplatin, and docetaxel (FLOT) is one of the preferred perioperative chemotherapy regimens in locally advanced resectable gastric cancer (GC). Till date, there are very few published data from India, regarding the outcomes of this relatively well-tolerated biweekly triplet regimen as first-line palliative chemotherapy in metastatic gastric or gastroesophageal junction (GEJ) adenocarcinoma.Materials and Methods In the present retrospective study, we evaluated the efficacy and safety of first-line FLOT regimen in Indian patients with HER2-negative metastatic adenocarcinoma of stomach or GEJ. The primary endpoint was overall survival (OS). Progression-free survival (PFS), overall response rate (ORR), and toxicity profile were taken as secondary endpoints.Results Between January 2021 and June 2024, 88 patients were treated with FLOT. The median age was 52 years (range, 23–68); 69.3% were males and 37.5% of the patients had ≥ 3 metastatic disease sites involvement at baseline. Dose reductions due to toxicity were required in 25% of the patients. The ORR was 68.2%; median PFS and OS were 6.3 months (95% confidence interval [CI]: 5.3–7.4) and 12.5 months (95% CI: 11.3–14.2), respectively. The most frequent grade 3 to 4 adverse events were diarrhea (15.9%), fatigue (13.6%), and neutropenia (12.5%). Younger patients (aged < 55 years) had much less ≥ grade 3 diarrhea (7.5%, n = 4), compared with patients aged ≥ 55 years (28.6%, n = 10). There was one toxicity-related death.Conclusion In the present study, biweekly FLOT regimen with primary prophylactic granulocyte colony-stimulating factor demonstrated encouraging efficacy with a favorable nongastrointestinal toxicity profile in Indian patients with HER2-negative metastatic gastric or GEJ adenocarcinoma. Clearly, this well-tolerated triplet regimen should be explored further through large prospective randomized trials in Asian patients.
Keywords: gastric cancer; systemic chemotherapy; FLOT regimen